2008
DOI: 10.1016/j.pain.2007.08.030
|View full text |Cite
|
Sign up to set email alerts
|

Selective stimulation of GalR1 and GalR2 in rat substantia gelatinosa reveals a cellular basis for the anti- and pro-nociceptive actions of galanin

Abstract: Galanin modulates spinal nociceptive processing by interacting with two receptors, GalR1 and GalR2. The underlying neurophysiological mechanisms were examined by whole-cell recording from identified neurons in the substantia gelatinosa of young adult rats. GalR1 was activated with a 'cocktail' containing the GalR1/2 agonist, AR-M 961 (0.5 microM), in the presence of the GalR2 antagonist, M871 (1.0-2.5 microM). GalR2 was activated with the selective agonist, AR-M 1896 (0.5-1.0 microM). Application of the 'GalR1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
34
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 41 publications
2
34
2
Order By: Relevance
“…Galanin also reduced the peak amplitudes of the monosynaptic A␦-fiber and C-fiber EPSCs evoked by stimulating the dorsal root in Ͼ70% of the SG neurons examined. This result is consistent with the observation that galanin reduces the peak amplitudes of EPSCs evoked in SG neurons by stimulating the dorsal root entry zone in young adult rats (Alier et al 2008). This primary afferentevoked EPSC amplitude reduction is presynaptic in origin, because the sEPSC amplitude is unaffected by galanin.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Galanin also reduced the peak amplitudes of the monosynaptic A␦-fiber and C-fiber EPSCs evoked by stimulating the dorsal root in Ͼ70% of the SG neurons examined. This result is consistent with the observation that galanin reduces the peak amplitudes of EPSCs evoked in SG neurons by stimulating the dorsal root entry zone in young adult rats (Alier et al 2008). This primary afferentevoked EPSC amplitude reduction is presynaptic in origin, because the sEPSC amplitude is unaffected by galanin.…”
Section: Discussionsupporting
confidence: 92%
“…This result may be consistent with the presence of GalR2 and GalR3 mRNAs in the rat spinal cord and DRG (O'Donnell et al 1999;Waters and Krause 2000). Alier et al (2008) have reported that galanin 2-11 dominantly increases the inter-event interval of sEPSC (decreases sEPSC frequency). Although a reason for the discrepancy between their study and our study is unknown, this may be due to a difference in the age of the rats used or distinct types of the neurons tested.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations